Performance Assessment Using Balance Scorecard in Kosika Gorontalo State University Students - Zulkifli Bokiu; Hartati Tuli; Lukman Pakaya (Journal of International Conference Proceedings (JICP), 2018)
Koperasi are one sector of the economy which has several members large community that has a goal to prosper the cooperative members. Form this effort is most in accordance with the mandate of the 1945 Constitution article 33 ayat (1) which reads the economy is structured as a joint effort on the principle of family. To increase cooperative business development in the future, always need to evaluate of the performance of cooperatives from one period to the next period. Information obtained from performance assessments is used to conduct evaluations to the performance of the previous period as a basis for making improvements in the period next. So far the performance appraisal is still limited to financial performance, by hence it is necessary to conduct performance assessments related to non-financial matters. This study aims to determine the performance with the balance score card. Stages in this study is to obtain performance information from 4 (four) perspectives. The results of the study indicate that (1) financial perspective; Kosika has good development of SHU, Capital, and ROA, (2) membership perspective; the growth in the number of members is seen to decline, SHU is accepted by members, the number of loans which is channeled through members seems to increase, (3) business process perspective internal loan service process, internal control, financial information is repaired continuously and regularly held annual member meetings, (4) learning and growth perspective; incentives received by employees, administrators, and supervisors always increase, salaries received by employees who have above the Provincial UMR, as well as training followed by administrators every year for increase management of cooperatives. Trend analysis in four perspectives between ponuwa UNG cosika with two other koperasi in Gorontalo city shows that cosika still has a better value than the other two cooperatives. Keywords: performance, balance scorecard, finance, non-finance, cooperatives